The neuroanatomy of Eml1 knockout mice, a model of subcortical heterotopia. Issue 3 (7th June 2019) - Collins, Stephan C.; Uzquiano, Ana; Selloum, Mohammed; Wendling, Olivia; Gaborit, Marion; Osipenko, Maria; Birling, Marie‐Christine; Yalcin, Binnaz; Francis, Fiona
Abstract: The cerebral cortex is a highly organized structure responsible for advanced cognitive functions. Its development relies on a series of steps including neural progenitor cell proliferation, neuronal migration, axonal outgrowth and brain wiring. Disruption of these steps leads to cortical malformations, often associated with intellectual disability and epilepsy. We have generated a new resource to shed further light on subcortical heterotopia, a malformation characterized by abnormal neuronal position. We describe here the generation and characterization of a knockout (KO) mouse model for Eml 1, a microtubule‐associated protein showing mutations in human ribbon‐like subcortical heterotopia. As previously reported for a spontaneous mouse mutant showing a mutation in Eml 1, we observe severe cortical heterotopia in the KO. We also observe abnormal progenitor cells in early corticogenesis, likely to be the origin of the defects. EML 1 KO mice on the C57BL/6N genetic background also appear to present a wider phenotype than the original mouse mutant, showing additional brain anomalies, such as corpus callosum abnormalities. We compare the anatomy of male and female mice and also study heterozygote animals. This new resource will help unravel roles for Eml 1 in brain development and tissue architecture, as well as the mechanisms leading to severe subcortical heterotopia.